Reading of images and production of texts written in english, among high school students - Quispe Estela, Omar Alfredo (2019)
Objective. To demonstrate the influence of reading images in the production of texts written in English for students in Fourth Grade of High School from Gran Unidad Escolar Leoncio Prado of Huánuco. Method. An experimental study was developed, with a quantitative approach and a quasi-experimental design. The sample comprised 58 students from Gran Unidad Escolar Leoncio Prado of Huánuco, 30 for experimental group and 28 for control group. Prior parents or guardians’ consent. An observation guide was applied to measure the influence of reading images in the production of texts written in English. This guide was previously validated. The hypothesis was verified using the Wilcoxon test, considering a p <= 0.05. In addition, ethical considerations were taken into account. Results. In the entrance test, the percentages for development of text production are similar in both experimental and control groups, with 90 % and 93 % respectively. In the exit test, on the contrary, the experimental group managed to develop text production in 87 %, and the control group 7 %. This indicates that the experimental group managed to improve their results significantly. Conclusion. Results demonstrated that students developed a reading of images capacity for production of texts in 87 %. Therefore, reading of images significantly influences the production of texts written in English.